Other, othering, otherness - Fourie, Alan Llewellyn (Rhodes University, 2026)
This qualitative exploratory study examined how Traditional Healers in South Africa understand and work with experiences of other, othering and otherness—concepts central to psychological theory. Nine Traditional Healers from AmaXhosa and AmaZulu traditions participated in semi-structured interviews, representing both rural and urban practice settings. The research addresses a critical gap in South African psychology by integrating historically marginalised indigenous healing knowledge with analytical psychology frameworks. This integration responds to the increased prevalence of othering phenomena in post-apartheid South Africa, ongoing theoretical debates about otherness, urgent calls for decolonising psychology, and analytical psychology's historical engagement with indigenous healing dating back to Jung's work. Using an interpretivist research paradigm and qualitative case study design, thematic analysis revealed two overarching themes: (1) Alterity and Othering Within—internal subjective experiences; and (2) Alterity and Othering Without—external experiences relating to society, family, other healers, and clinical work. Each theme contains subthemes of Separateness with Connection and Agency, as well as Separateness, Unconnected, and No Agency, revealing that othering is central to the identity formation of Traditional Healers, including their calling (ukutwasa), spiritual development, and therapeutic practice. Findings demonstrate that Traditional Healers have sophisticated, culturally grounded frameworks for understanding other, othering and otherness which parallel and extend analytical psychology concepts, including individuation, the ego-Self relationship, the collective unconscious, synchronicity, projection, and shadow work. Their practices emphasise ritual engagement, boundary maintenance, and a sustained relationship with otherness, rather than complete integration—offering important corrections to mainstream psychology. The study makes three central contributions: highlighting traditional healing as a parallel form of psychological knowledge; establishing analytical psychology as a theoretical bridge between Western frameworks and traditional healing; and demonstrating its transformative potential for addressing contemporary phenomena of othering. Implications include incorporating alterity experiences in clinical training, developing collaborative practice models, and advancing psychology's decolonisation in South Africa. Future research should expand to larger samples using collaborative methodologies that position Traditional Healers as co-researchers throughout all phases of the research.
an exploratory analytical psychology study with traditional healers
Keywords: Healers (http://id.loc.gov/authorities/subjects/sh85059504); Ethnoscience (http://id.loc.gov/authorities/subjects/sh96010624); Pscyhology; Analytical psychology (https://www.wikidata.org/wiki/Q245179); Other (https://www.wikidata.org/wiki/Q1433373); Alterity (https://www.wikidata.org/wiki/Q583580); Traditional knowledge (https://www.wikidata.org/wiki/Q1428168)